Implementasi Sistem Penjualan Bahan Bangunan Menggunakan Metode Rad Toko Merah Delima - Maria F. Hostika Hangga; Gergorius Kopong Pati; Diana Reby Sabawaly (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
Building materials sales are an important sector in the construction industry, which requires an efficient system to manage transactions, inventory, and customer relationships. In an effort to improve the performance and efficiency of the sales process, this study proposes the implementation of a building material sales system using the Rapid Application Development (RAD) method at Toko Merah Delima. The RAD method was chosen for its ability to speed up the application development process with an iterative approach that involves direct user feedback. This research aims to design and implement a system that can automate the sales process, monitor stock of goods, and produce reports that can be accessed easily. The developed system includes integrated sales transaction management features, stock management, and sales reports. The results of the implementation of this system show increased efficiency in the management of transactions and stock of goods, as well as making it easier to monitor sales reports in real-time. By using the RAD method, this system can be developed in a shorter time and more in accordance with the operational needs of the store. This research is expected to contribute to the development of information systems for the building materials trading industry.